Model Pembelajaran Inqury untuk Meningkatkan Kemampuan Akademik Anak di Sekolah dalam Memecahkan Masalah - Dwi Nugraini; Amanda Anggi Pramaishella; Ika Putri Mei Surya (Indonesian Publication Center, 2023)
Education is the most important thing in human life, meaning that every Indonesian has the right to receive it and is expected to continue to develop it, education never stops, education in general makes sense in the process in life around developing individuals to be able to live life. One of the lessons that can be used in elementary schools in the learning process is the study of science. The learning model that can encourage students to find or understand information is the inquiry learning model. This learning model involves students fully during the learning process so that students are expected to be able to examine existing problems and find their own solutions to these problems. Based on this description, this article aims to determine the importance of using an inquiry-based learning model to improve students' ability to solve problems. This research is a descriptive study with a qualitative approach, with data collection techniques using interviews and observations. The results of the academic ability of students who were taught by the inquiry method showed that students were able to solve the problem well. Learning outcomes are getting better by using the inquiry method. The results of this study are not only guided by academic improvement, but by teaching ways to find knowledge to students through observation and problem solving.